2013
DOI: 10.1016/j.intfin.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the state of financial stability

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 42 publications
(25 reference statements)
0
52
0
Order By: Relevance
“…Instead of lagging explanatory variables, we define the dependent variable as a forecast horizon that includes a specified number of quarters prior to the event (8 quarters in the benchmark case). In order to account for the so‐called crisis and postcrisis bias (e.g., Bussire & Fratzscher, ; Sarlin & Peltonen, ), we exclude crisis and postcrisis periods from the estimation sample. As economic variables go through adjustment processes prior to reaching tranquil paths in times of crisis and recovery, these periods are not informative for identifying the path from precrisis regimes to crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of lagging explanatory variables, we define the dependent variable as a forecast horizon that includes a specified number of quarters prior to the event (8 quarters in the benchmark case). In order to account for the so‐called crisis and postcrisis bias (e.g., Bussire & Fratzscher, ; Sarlin & Peltonen, ), we exclude crisis and postcrisis periods from the estimation sample. As economic variables go through adjustment processes prior to reaching tranquil paths in times of crisis and recovery, these periods are not informative for identifying the path from precrisis regimes to crisis.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from credit variables, Table 1 shows that credit‐related indicators have been included in all studies and most have also found one or several of them to be successful, such as credit‐to‐GDP gap by Borio and Lowe (2002) and similar global measures by Alessi and Detken (2011). Likewise, asset prices have been oftentimes both included in assessments and found significant, such as the deviation from trend of an aggregated asset price index by Borio and Lowe (2002) and deviation from trend of stockmarket capitalization to GDP by Lo Duca and Peltonen (2013) and Sarlin and Peltonen (2013). While financial regulation and financial sector size have been accounted in only a few studies, money aggregates have been used more frequently.…”
Section: Methodsmentioning
confidence: 99%
“…From the viewpoint of the applied methods, the studies have generally used signal extraction (also called the signaling approach) and multivariate logit or probit analysis. For instance, while Kaminsky and Reinhart (1999), Borio and Lowe (2002), Alessi and Detken (2011) and Lo Duca and Peltonen (2013) make use of signal extraction, Schularick and Taylor (2012), Lo Duca and Peltonen (2013) and Sarlin and Peltonen (2013) use logit or probit analysis. Moreover, the set of studies in Table 1 also included Self‐Organizing Maps (Sarlin & Peltonen, 2013), standard linear OLS regression (Kauko, 2012) and Bayesian Model Averaging (Babecký et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…(). More closely related to the topic of visual dynamic clustering, Sarlin and Peltonen () introduced a self‐organizing map (SOM)‐based approach to mapping financial stability at the country level. Likewise, early applications of the SOM aimed at mapping banks based upon their financial ratios (Serrano‐Cinca, ).…”
Section: Introductionmentioning
confidence: 99%
“…A simple, yet commonly used, approach is a radar-chart visualization of six composite risk and condition indices, as outlined by Dattels et al (2010). More closely related to the topic of visual dynamic clustering, Sarlin and Peltonen (2013) introduced a self-organizing map (SOM)-based approach to mapping financial stability at the country level. Likewise, early applications of the SOM aimed at mapping banks based upon their financial ratios (Serrano-Cinca, 1996).…”
Section: Introductionmentioning
confidence: 99%